Knowledge and usage patterns of clotrimazole vaginal cream and tablet amongst females: a cross-sectional study - Adigwe, Obi Peter; Onavbavba, Godspower; Okeke, Chiamaka Frances (Frontiers in Pharmacology, 2025)
IntroductionClotrimazole is a broad-spectrum antimycotic agent that is primarily used to treat yeast and other fungal infections. Considering the limited number of medicines available for the treatment of vulvovaginal candidiasis, indiscriminate use of clotrimazole is rapidly emerging as a critical health issue. In Nigeria, where clotrimazole can be obtained without a prescription, there are public health concerns regarding the potential for antimicrobial resistance. This study therefore aimed to assess the knowledge and usage patterns of clotrimazole amongst women.MethodsA cross-sectional study involving 410 adult females in the Federal Capital Territory was conducted using a validated questionnaire. Data collected were analysed using Statistical Package for Social Sciences version 25. Descriptive statistics were used to summarise sociodemographic data, knowledge scores and usage patterns, while inferential statistics (ANOVA and t-test) examined associations between participants’ socio-demographic characteristics and knowledge levels.ResultsThe study included participants aged 18 years and above. Majority of the respondents learned about clotrimazole in the hospital (68.8%) and pharmacy (63.2%). Using Bloom’s cut off point, none of the participants had good knowledge of clotrimazole, and only about a quarter of the participants (26.1%) reported average knowledge regarding the use of the medicine. The overall mean knowledge score was 6.45 ± 2.43 (range 0–14). About a third of the respondents (31.7%) who had used clotrimazole in the last year reported using the medicine as a contraceptive. There was a statistically significant relationship between the level of education and participants’ knowledge score (p < 0.001).ConclusionFindings from this study revealed that the participants had poor knowledge regarding clotrimazole use. Inappropriate usage patterns were also observed. These emergent findings have serious implications, particularly regarding the potential for resistance to the medicine.